Praktik Pedagogis Guru dalam Penanganan Kasus Bullying - Dinda Amalia Nasution; Agnes Damanik; Susi Krisdayanti Marbun; Rupma Riana Saragih; Sarah Theresia Zega; Ari Yohanes Manik; Jamaludin Jamaludin (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
Bullying is one of the problems that often arise in the school environment and is a serious problem in education. In this case, the role of schools as educational institutions in preventing this problem is needed. Teachers as the main actors of the educational process are highly responsible for creating a safe and comfortable learning environment for all students. This study aims to determine the duties of teachers and provide strategic recommendations to improve the effectiveness of dealing with bullying in schools. This study also contributes to the development of more effective educational policies in the prevention and treatment of bullying cases at the secondary school level. The research method in this study used a qualitative approach with a case study design. Data recording techniques were conducted by in-depth observation and document analysis in relation to school guidelines related to bullying. Teachers have a huge influence in preventing bullying with important outcomes such as the creation of a respectful and safe school culture, increased student understanding of the dangers of bullying, positive changes in student behavior, increased courage to report bullying cases, and improved quality of life for students. Thus, providing support to teachers in bullying prevention efforts is fundamental to building a positive learning environment and effectively addressing bullying issues in schools..